The efficacy and safety of neoadjuvant chemoradiotherapy combined with immunotherapy for locally advanced rectal cancer patients: a systematic review - Yang, Lei; Cui, Xiujing; Wu, Fengpeng; Chi, Zifeng; Xiao, Linlin; Wang, Xuan; Liang, Zezheng; Li, Xiaoning; Yu, Qiyao; Lin, Xueqin; Gao, Chao (Frontiers in Immunology, 2024)
Background Several studies have explored the effectiveness of PD-1/PD-L1 inhibitors combined with neoadjuvant chemoradiotherapy (nCRT) in the treatment of locally advanced rectal cancer(LARC), particularly in microsatellite stable(MSS) or mismatch repair proficient(pMMR) LARC patients. We undertook a single-arm systematic review to comprehensively evaluate the advantages and potential risks associated with the use of PD-1/PD-L1 inhibitors in conjunction with nCRT for patients diagnosed with locally advanced rectal cancer. Methods The PubMed, Embase, Cochrane Library, ClinicalTrials.gov, ASCO and ESMO were searched for related studies. The main outcomes were pathologic complete response (pCR), major pathological response (MPR), anal preservation, and adverse effects (AEs). Results Fourteen articles including 533 locally advanced rectal cancer (LARC) patients were analyzed. The pooled pCR, MPR, and anal preservation rates were 36%, 66% and 86%. Grade ≥3 adverse events occurred in 20%. Subgroup analysis showed that; dMMR/MSI-H had a pooled pCR (100%) and MPR (100%), pMMR/MSS had a pooled pCR (38%) and MPR (60%); the short-course radiotherapy and long-course radiotherapy had pooled pCR rates of 51% and 30%, respectively. The rates of pCR for the concurrent and sequential immuno-chemoradiotherapy subgroups at 30% and 40%, mirroring pCR rates for the PD-L1 and PD-1 inhibitor subgroups were 32% and 40%, respectively. Conclusion In cases of locally advanced rectal cancer, PD-1/PD-L1 inhibitors combined with neoadjuvant chemoradiotherapy have shown promising response rates and acceptable toxicity profiles. PD-1/PD-L1 inhibitors combined with neoadjuvant chemoradiotherapy hence has a positive outcome even in MSS LARC patients. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42023465380.